2020
DOI: 10.3126/janr.v3i1.27102
|View full text |Cite
|
Sign up to set email alerts
|

Value chain analysis of Large Cardamom (Amomum subulatum Roxburg) in Bhojpur, Nepal

Abstract: Large Cardamom is a high value spice crop having substantial export potential. The study was conducted on Feb-May, 2019 in Arun rural municipality, Bhojpur municipality and Sadananda municipality with an objective to analyze existing value chain of Large Cardamom in Bhojpur district of Nepal.  In total, 150 Large Cardamom growers were selected using purposive sampling technique. In addition to that, 17 traders from the Bhojpur, Khadbari and Birtamod were also selected for the study. Findings showed that farmer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…This indexing technique was used to calculate the constraints associated with potato production in the Terai region and wheat production (Subedi et al, 2019a;Subedi et al, 2019b). Similarly, this technique for ranking of marketing problems in large cardamom and seed production & marketing constraints in maize respectively (Joshi and Kalauni, 2020;Shrestha and Shrestha, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This indexing technique was used to calculate the constraints associated with potato production in the Terai region and wheat production (Subedi et al, 2019a;Subedi et al, 2019b). Similarly, this technique for ranking of marketing problems in large cardamom and seed production & marketing constraints in maize respectively (Joshi and Kalauni, 2020;Shrestha and Shrestha, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Kalauni and Joshi also observed that the famers in the region of study area were not performing the grading and polishing value adding steps (Kalauni and Joshi, 2020). Curing is also an important step for large cardamom processing and it is usually done using traditional bhattis made by locally available materials requiring no scientific knowledge (Singh and Pothula, 2013;Bhutia and Sharangi, 2018).…”
Section: Value Chain and Marketing Trendmentioning
confidence: 99%
“…According to the farmers, an extra charge is added while performing the tail cutting using machine or scissors (Singh and Pothula, 2013). So, majority of the farmers perform it in the traditional way of massaging the produce (Kalauni and Joshi, 2020).…”
Section: Value Chain and Marketing Trendmentioning
confidence: 99%
See 2 more Smart Citations